Experience Economy dalam Industri Blind Box: Studi Kasus Strategi Pemasaran POP MART pada Generasi Z - Muhammad Burniat; Faisal Bagus Aji Apriliawan; Dian Wahyu Nurjanah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the experience-based marketing strategies implemented by POP MART through the Experience Economy model, which consists of four dimensions: Entertainment, Education, Escapist, and Aesthetic experiences. As competition in the creative collectible industry intensifies, companies are increasingly required to create memorable and emotionally engaging customer experiences rather than relying solely on product quality or functional value. POP MART has successfully transformed collectible toys into experiential products by integrating storytelling, limited-edition collections, and immersive retail environments that strengthen consumer-brand relationships. This research employs a qualitative approach using an instrumental case study design. Data were collected from secondary sources, including POP MART’s official website, the company’s annual reports, official social media platforms, industry publications, and relevant scientific literature. The data were analyzed using thematic analysis based on the Experience Economy 4E framework proposed by Pine and Gilmore. The findings indicate that POP MART creates entertainment experiences through blind box concepts, unboxing activities, and secret figure mechanisms that generate excitement and anticipation. Educational experiences are developed through character storytelling, collection information, and intellectual property knowledge that enrich consumers’ understanding of the brand. Escapist experiences emerge from collecting activities, fan communities, interactive events, and immersive brand experiences that encourage active consumer participation. Meanwhile, aesthetic experiences are reflected in distinctive character designs, premium packaging, visually appealing retail stores, and a consistent brand identity. The integration of these four experiential dimensions creates a holistic brand experience that enhances customer engagement, emotional attachment, satisfaction, and loyalty while encouraging repeat purchases and positive word-of-mouth. These findings demonstrate that the Experience Economy serves as a significant source of POP MART’s competitive advantage in attracting and retaining Generation Z consumers in the rapidly growing designer toy market.